2012
DOI: 10.1111/j.1365-2389.2012.01469.x
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Streptococcus suis on various soil particles from an Alfisol and effects on pathogen metabolic activity

Abstract: The potential contamination of soil environments by pathogens from agricultural manures has received great attention in recent years. However, few studies of the sorption and metabolic activity of pathogens on soil particles have been conducted to date. In this study, we investigated the sorption of pathogen Streptococcus suis on various soil particles from an Alfisol as a function of pH and calcium chloride (CaCl2) concentration. S. suis metabolic activity in the presence of different soil particles was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The adhesion of E. coli to soil colloids decreased with increasing pH, which agreed with previous studies (Wu et al 2011a;Zhao et al 2012a). Zhao et al (2012a) found that the adhesion of S. suis to soil particles decreased as the pH rose from 4.0 to 9.0.…”
Section: Adhesion Of E Coli To Soil Colloidssupporting
confidence: 91%
See 2 more Smart Citations
“…The adhesion of E. coli to soil colloids decreased with increasing pH, which agreed with previous studies (Wu et al 2011a;Zhao et al 2012a). Zhao et al (2012a) found that the adhesion of S. suis to soil particles decreased as the pH rose from 4.0 to 9.0.…”
Section: Adhesion Of E Coli To Soil Colloidssupporting
confidence: 91%
“…Zhao et al (2012a) found that the adhesion of S. suis to soil particles decreased as the pH rose from 4.0 to 9.0. Wu et al (2011a) also observed that P. putida adhesion to soil particles was reduced by 44.0-78.8% when the pH was increased from 4.0 to 9.0.…”
Section: Adhesion Of E Coli To Soil Colloidsmentioning
confidence: 97%
See 1 more Smart Citation
“…coli and full EPS-S. suis remained constant (P N 0.05), while only the full EPS-E. coli increased slightly by 3.2 mV. This result suggests that the compression of the double layer is effectively achieved around 60 mM (Mills et al, 1994;Zhao et al, 2012). Similar results were also observed in literature that the zeta potentials of E. coli O157:H7 and Salmonella pullorum SA1685 were unchanged (P N 0.05) at high IS conditions (Castro and Tufenkji, 2007;Haznedaroglu et al, 2009).…”
Section: Charge Properties Of Bacteria and Soilmentioning
confidence: 98%
“…These phenomena are important to understand the fate of pathogens in terms of immobilization and metabolic activity, especially if these are responsible for serious diseases of animal and humans. Zhao et al (2012) focused specifically on the sorption of Streptococcus suis on various soil particles, and effects on the metabolic activity of the sorbed pathogen. Sorption of this microorganism was greater on clay particles, with little effect of organic matter coatings, and depended especially on electrostatic forces and electrosteric effects at large Ca 2+ concentrations.…”
Section: Biological Interactionsmentioning
confidence: 99%